Multidisciplinary decision-making in older patients with cancer, does it differ from younger patients?. Issue 10 (October 2021) - Festen, S.; Nijmeijer, H.; van Leeuwen, B.L.; van Etten, B.; van Munster, B.C.; de Graeff, P.
Abstract: Background: In order to tailor treatment to the individual patient, it is important to take the patients context and preferences into account, especially for older patients. We assessed the quality of information used in the decision-making process in different oncological MDTs and compared this for older (≥70 years) and younger patients. Patients and methods: Cross-sectional observations of oncological MDTs were performed, using an observation tool in a University Hospital. Primary outcome measures were quality of input of information into the discussion for older and younger patients. Secondary outcomes were the contribution of different team members, discussion time for each case and whether or not a treatment decision was formulated. Results: Five-hundred and three cases were observed. The median patient age was 63 year, 32% were ≥70. In both age groups quality of patient-centered information (psychosocial information and patient's view) was poor. There was no difference in quality of information between older and younger patients, only for comorbidities the quality of information for older patients was better. There was no significant difference in the contributions by team members, discussion time (median 3.54 min) or number of decision reached (87.5%). Conclusion: For both age groups, we observed a lack of patient-centered information. The only difference between the age groups was for information on comorbidities. There were also no differences in contributions by different team members, case discussion time or number of decisions. Decision-making in the observed oncological MDTs was mostly based on medical technical information. Highlights: The discussion in oncological MDTs was compared between older and younger patients. Quality of patient-specific information was poor in both age groups. Only information about comorbidities was better for older patients. The observed oncological MDTs mostly discussed medical technical information. Patient-specific information is needed for patient centered decision-making.